Proceedings of the Fourth ACM Conference on Recommender Systems 2010
DOI: 10.1145/1864708.1864740
|View full text |Cite
|
Sign up to set email alerts
|

Automatically building research reading lists

Abstract: All new researchers face the daunting task of familiarizing themselves with the existing body of research literature in their respective fields. Recommender algorithms could aid in preparing these lists, but most current algorithms do not understand how to rate the importance of a paper within the literature, which might limit their effectiveness in this domain. We explore several methods for augmenting existing collaborative and content-based filtering algorithms with measures of the influence of a paper with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 19 publications
5
81
1
Order By: Relevance
“…In this evaluation, CBF outperformed CF, contradicting the previous offline results from Torres et al In 2010, Ekstrand et al found that CBF performed worse than CF in both an offline evaluation and a user study, which again did not align with the previous findings [26].…”
Section: Reproducibility and The Butterfly Effectcontrasting
confidence: 94%
See 4 more Smart Citations
“…In this evaluation, CBF outperformed CF, contradicting the previous offline results from Torres et al In 2010, Ekstrand et al found that CBF performed worse than CF in both an offline evaluation and a user study, which again did not align with the previous findings [26].…”
Section: Reproducibility and The Butterfly Effectcontrasting
confidence: 94%
“…Some of the approaches were evaluated using both an offline evaluation and a user study. In two evaluations, results from the offline evaluations were indeed similar to results of the user studies [26,84]. However, the user studies had five and 19 participants, respectively, which led to statistically insignificant results.…”
Section: Offline Evaluationsmentioning
confidence: 51%
See 3 more Smart Citations